2018
DOI: 10.1159/000486423
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cardiac Output in Pulmonary Hypertension Using Impedance Cardiography

Abstract: Background: Cardiac output (CO) is a prognostic factor in pulmonary hypertension (PH). Right heart catheterisation using the direct Fick method or thermodilution (TD) is the reference technique for CO measurement. Impedance cardiography (IPc) is a known non-invasive method of measuring CO. Objectives: In our study, we assume that the measurement of CO by IPc using the PHYSIOFLOW® system is as accurate as TD or using the direct Fick method in patients with PH in group 1 or group 4. Methods: A total of 75 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…Impedance cardiography (ICG) is a noninvasive method of evaluating SV based on measurement of the thoracic bioimpedance. [8][9][10][11][12][13] Being a noninvasive method, ICG can be performed repeatedly, even in the outpatient clinic setting. Furthermore, sequential measurements of A trial fibrillation (AF), the most common sustained tachyarrhythmia observed in clinical practice, is related to potentially serious complications and death.…”
mentioning
confidence: 99%
“…Impedance cardiography (ICG) is a noninvasive method of evaluating SV based on measurement of the thoracic bioimpedance. [8][9][10][11][12][13] Being a noninvasive method, ICG can be performed repeatedly, even in the outpatient clinic setting. Furthermore, sequential measurements of A trial fibrillation (AF), the most common sustained tachyarrhythmia observed in clinical practice, is related to potentially serious complications and death.…”
mentioning
confidence: 99%
“…In other words, for a true CO value of 5.5 L/min, the estimation of CO using IPc could range from 3.0 to 7.0 L/min assuming that the DF measure is close enough to the true value. Dupuis et al [1] also demonstrated PEs of 22.5 and 21% for IPc when compared to DF and TD, respectively. The narrow PEs are inconsistent with the wide LoA obtained from the Bland-Altman plot.…”
mentioning
confidence: 96%
“…In their article published in this issue of Respiration , Dupuis et al [1] compared impedance cardiography (IPc) with DF and TD in a population of pulmonary hypertension patients. They concluded that IPc is reliable compared to the DF and TD methods.…”
mentioning
confidence: 99%
See 2 more Smart Citations